The Study of the Deforming Regime of AC/AC Converter using Fourier and Multiresolution Analysis - Rata, G.; Norkevicius, P.; Rata, M. (Elektronika ir Elektrotechnika, 2012)
For electric power quality improvement should be identified and followed the deforming consumers. This is necessary, because the number of equipments producing harmonic distortion is increasing, primarily by expanding the use of static power converters. This paper presents the study of the deforming state generated by the AC/AC converter with full-wave AC control using two SCRs (silicon – controlled rectifier) connected in inverse parallel. The harmonic spectrums of distorted current and voltage signals are determined by the load and the thyristors delay angle. For this study, we use Fourier and Wavelet transform. A multiresolution signal decomposition technique is presented in the analysis of the deforming signals from the AC/AC converter. Ill. 10, bibl. 8 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.121.5.1643